Intertextuality and Subversion: Poems by Ana Rossetti and Amparo Amorós - Andrew P. Debicki (Studies in 20th & 21st Century Literature, 1993)
In the last two decades, a number of Spanish women poets have written very significant works which use intertextuality to lead their readers into new perspectives and attitudes toward literary and social conventions. By examining two texts by Rossetti and Amorós that use intertexts to undermine, respectively, traditional "carpe diem" poetry and sexually allusive verse of different kinds, the article suggests that they reflect new, post-modern literary currents.
Keywords: Spanish poetry; women poets; Spanish women poets; intertextuality; literary conventions; social conventions; Ana Rossetti; Amparo Amorós; carpe diem; sexual; post-modern